Anwendungsreif? Nutzung und Potenzial von digitalen Geodaten für Stadtforschung und Raumbeobachtung am Fallbeispiel OpenStreetMap - Plennert, Matthias (Stadtforschung und Statistik, 2016)

The social construction of technological stasis: The stagnating data structure in OpenStreetMap - Plennert, Matthias (Big Data & Society, 2018)
The article aims for examining the ‘technological stasis’ of the data structure in OpenStreetMap – the successful global collaborative geodata project devoted to ‘create and distribute free geographic data for the world’. Digital structures are strongly influenced by continuing stagnation. This technological stasis – the lack of change in technology – influences data in various ways, as demonstrated by the intensive discussion of the issue by computer scientists and software engineers. However, existing research describing stagnating software is often technic centred and fuzzy, while critical research is barely considering issues of technological stasis in the digital context at all. Therefore, this paper aims for enriching this body of knowledge in order to shed light on aging data structures. I reframe technological stasis with a social-constructivist perspective – using the approach of Social Construction of Technology – especially with the concept of technological frames. Based on the case example of OpenStreetMap, my findings suggest that the data structure – and its stasis – is the outcome of competing understandings and perspectives, shaped by power asymmetries. Although the data structure did not significantly change for more than 10 years, I demonstrate that this is not because of a lack of motivation, nor technological difficulties of carrying out such changes. The technological stasis is rather rooted in the dominant position of few project members who are able to change the software design; it is their perception of the project that defines how data should be stored and what features are dispensabl
Keywords: Social construction of technology; technological frames; OpenStreetMap; legacy software; technological stasis; data structure

The Socio-Technical Background of an Unconventional Software Architecture in OpenStreetMap: Understanding the Implementation of ‘Folksonomy - Glasze, Georg; Plennert, Matthias; Schlieder, Christoph (Computational Culture, 2019)
Previous software studies have stressed the socio-technical origin and embeddedness of software; hence specific socio-technical contexts are always inscribed into the digital structure. Inspired by the observation that the software architecture in OpenStreetMap (OSM) differs fundamentally from well-established conventions in the geospatial field, namely using folksonomies as an attribution system, this paper exposes and records the digital remains of the software development process within this successful, open and voluntary geodata project. We aim to reveal the socio-technical background of this software feature by analyzing digital archives of communication and coding in OSM with a combination of qualitative and quantitative methods. Thus we trace this specific feature through the entire processes of technological and social negotiations as well as the implementation. Our findings show that there were several competing technologies within the project; the final decision towards one of them was based on a do-ocracy — those who do the coding work get to decide how it’s done - and thus independently from discussions on the main communication medium: the OSM mailing list. We argue that the communication on the mailing list conceals the de-facto oligarchic environment of technological decision-making: contributors without the necessary technical skills for participating in the software development are only allegedly able to get involved in discussions regarding the technological orientation of OSM.
Keywords: OpenStreetMap; Volunteered Geographic Information; Software Studies; Digital Geography